A movement receptor of the small intestine - Bessou, P. (1966)
1. The characteristics of a mechanoreceptor of the small intestinal region of the cat were studied by recording potentials from single afferent fibres in filaments dissected from mesenteric nerves. Forty-six fibres were examined in detail. Each of these was excited by light mechanical stimulation of the mesentery or small bowel, but none responded to sinusoidal vibration at frequencies above 100/sec. A `spontaneous' discharge was regularly observed and it appeared to be related to peristaltic intestinal activity. On the other hand, non-propulsive motor contractions of the intestinal musculature were poorly correlated with discharge frequency. 2. The region of maximal sensitivity of each fibre was determined by light pressure applied with a fine probe. Under these conditions the receptive field always resolved itself into 1-5 sensitive points (smaller than 1 mm in diameter). Each such point lay upon or immediately adjacent to a branch of the mesenteric artery supplying the area. Commonly, one or more sensitive spots were located at the place where a mesenteric artery entered the intestinal musculature. Localized pressure to one sensitive spot evoked a low frequency discharge (under 30/sec) which adapted within several seconds. A movement of the mesentery or the intestine distorting the region near one of the sensitive points regularly evoked a near maximal response. The dynamic phase of distension of the intestine by an intraluminal ballon also evoked a response. During inflation or deflation of the intestinal balloon, the frequency of discharge was positively correlated with both the rate of inflation and the pressure reached at the end of the dynamic phase. There was little relation between static distension and the discharge frequency. 3. The conduction velocity of each afferent fibre was determined by electrical stimulation of its mesenteric nerve. The majority of the fibres studied had conduction velocities between 5 and 10 m/sec, the range being 2-21 m/sec. These figures were taken to indicate that the fibres were myelinated and of small diameter. Histological determination of myelinated fibre diameter in the mesenteric nerves from which the recordings were taken suggested that the numerical factor relating fibre diameter in μ to conduction velocity in m/sec was under 6. 4. It was concluded that these receptors signalled movement of the intestine, regardless of its origin.